Problem-based learning applied in pedagogical models subject - Encalada Canacuan, Richard Adan; Mina Ortega, Marcelo René; Méndez Urresta, Jacinto Bolívar; Méndez Urresta, Edgar Marcelo (SATHIRI, 2019)
This research guides the Pedagogical and Didactic Fundamentals subject in the General Psychology Major immersed in Higher Education which can be determined by a process of education, different from the other methodologies that most of professors prioritize in this higher education field; therefore there is a contribution of a different methodology that is the PBL, Problem-Based Learning. It is used by the minority of university teachers in their classrooms as a theoretical practice, and it is a practical exercise of a demonstration class regarding to different pedagogical models related to Montenegro; being this an important variable of higher education in our university. As instruments of quantitative results, a Pre-test and Post-test process were considered, finishing with a survey to assess the PBL application by using the students"™ criteria, which means the application of assertiveness work knowledge in the performance of teaching and learning of all the university community, and the great challenges of professors inside and outside the corresponding classrooms. The objective of this study was to recognize the development of teaching using different pedagogical models by professors of this institution applying classroom participation and a context of the complementary units of a PBL methodological process.